Morphological and structural properties in graphene oxides and reduced graphene oxides - Bazán, A (2019)
In this work, graphite powder was used as initial material to obtain graphene oxides (GO). We propose the reduction of graphene oxides, by physical-chemical method, which consists in a thermo and chemical reduction in the presence of NaBH4 to obtain reduced graphene oxides (RGO). Furthermore, the presence of functional groups and the nanocrystal size were determined by Visive, FTIR and Raman spectroscopy in both samples, GO and RGO. Thereby, we observe that the use of physical-chemical method to obtain RGO produces a signicant defects decrease, shown by the D band of the Raman spectrum which practically disappear after this reduction. In addition to this, a morphological study made by AFM have shown relative ats surfaces in the nano-graphene samples obtained by the presented technique.